2001
DOI: 10.3998/ark.5550190.0002.a04
|View full text |Cite
|
Sign up to set email alerts
|

5-Nitropyridine-2-sulfonic acid, a new precursor for 2,5-disubstituted pyridines

Abstract: Oxidation of 5-hydroxyaminopyridine-2-sulfonic acid (1) to 5-nitropyridine-2-sulfonic acid (2) may be performed selectively by SPB in acetic acid, bleach in water or potassium permanganate in water, with the last as the preferred one. The structure of 2 was verified by X-ray crystallography. The crude products proved difficult to purify efficiently due to inorganic impurities, but substitution of the sulfonyl group in 2 with methanol yielded 2-methoxy-5-nitropyridine (6) in 44, 42 and 57 % overall yield from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Some time ago we reported the preparation of 5-nitro-2-pyridinesulfonic acid and its potassium salt (9) from 3-nitropyridine. 8 We have also reported the substitution of the sulfonate group by chloro, alkoxy and amino groups. 9 We have now reacted the potassium sulfonate 9 with the carbanion of methyl chloroacetate.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Some time ago we reported the preparation of 5-nitro-2-pyridinesulfonic acid and its potassium salt (9) from 3-nitropyridine. 8 We have also reported the substitution of the sulfonate group by chloro, alkoxy and amino groups. 9 We have now reacted the potassium sulfonate 9 with the carbanion of methyl chloroacetate.…”
Section: Discussionmentioning
confidence: 92%
“…), 2954 (m), 1676 (s), 1616 (s), 1578 (s), 1541 (s), 1344 (s), 1319 (s), 1297 (s), 1282 (s), 1249 (m); 1 13 C NMR (100 MHz; CDCl 3 )  168.8, 160.9, 149.6, 135.6, 42,1 (br. ), 41.9, 39.9, 31.7, 31.5, 20.3, 20.2, 14.0, 13.9; m/z (EI) 308.18458 (M + , C 15 H 24 N 4 O 3 requires 308.18484), 265 (9%), 263 (18), 262 (100), 206 (13), 192 (6), 166 (18), 148 (8), 120 (8); UV-Vis (EtOH):  max () 222 (8500), 335 (12500).…”
Section: -Butylamino-4-butylcarboxamidomethyl-5-nitropyridine (12c)mentioning
confidence: 99%
“…Both sodium metal and triethylamine were tried to generate phenoxide ions. 1 H NMR spectroscopy showed that no reaction took place.…”
Section: Substitution Reactions With Aminesmentioning
confidence: 99%
“…2b was reacted with aniline at room temperature and at 100 ЊC with DMF as solvent. 1 H NMR spectroscopy showed that no reaction took place.…”
Section: Substitution Reactions With Aminesmentioning
confidence: 99%
See 1 more Smart Citation